Smart card research and advanced applications : 17th International Conference, CARDIS 2018, Montpellier, France, November 12-14, 2018, Revised selected papers /: 17th International Conference, CARDIS 2018, Montpellier, France, November 12-14, 2018, Revised selected papers. (2019) - Unknown
No abstract available